How to turn 2wrong3 answer into learning - Association for Supervision and Curriculum Development (Alexandria, VA : ASCD, 2004)
This video program explores ways that effective teachers turn student's incorrect or unanticipated answers into learning opportunities. The exchange of questions and answers is a key element of the learning process, and its success depends on a classroom environment where students feel valued, where their answers are respected
Title from title screen
Keywords: Teaching; Teachers; Teaching and learning